CLINICAL REASONING AT THE EMERGENCY DEPARTMENT - Neves, Fábio F.; Pazin-Filho, Antônio (Medicina (Ribeirao Preto), 2008)
Clinical reasoning is the exercise of judging with uncertainty in the care of the patient. No medical environment is as unpredictable as to the emergency room, and the clinical reasoning is often hampered by several factors, such as the need for rapid decision-making, work overload, poorly trained staff, incomplete clinical data, frequent interruptions and patient’s poor collaboration. However, this environment often chaotic, concentrates the bulk density of decisions on medical practice, many of them vital. This article will use illustrative cases to describe the classic model of clinical reasoning, as well as other models that arise from the peculiarities of the emergency practice, in order to help developing self-assessment in the diagnostic process, seeking the reduction of avoidable errors.